Epidemiological study on chronotype among preschool children in Japan: Prevalence, sleep–wake patterns, and associated factors. (25th November 2016) - Doi, Yuriko; Ishihara, Kaneyoshi; Uchiyama, Makoto
ABSTRACT: Our current 24-h society and the weekday–weekend switch of our social clocks may affect young children's sleep and circadian rhythms. However, such evidence is scarce. We conducted a nationwide epidemiological study of sleep and health in preschool children aged 3–5 years attending kindergarten or childcare centers in Japan, using stratified one-stage cluster sampling. The target population was 2 969 627 individuals (as of 1 April 2013). The Children's ChronoType Questionnaire was used to measure chronotypes (morning (M)-type, neither (N)-type and evening (E)-type), and weekday and weekend sleep–wake parameters. Randomly sampled population estimates were obtained via respondents with a person-level weight, which accounted for survey responses and poststratification. Standard errors and 95% confidence intervals were adjusted for the complex survey design using jackknife estimation. A linear regression model of the correlation between chronotype and sleep–wake parameters and a multivariate logistic regression model for the links between chronotype and putative associated factors were used for statistical analyses. The estimated prevalence of M-, N- and E-types were 31.6%, 55.9% and 10.0%, respectively. The corresponding numbers of children were 937 910, 1 659 574 and 296 083. The remaining 2.5% was not specified. The proportions of children who woke up by themselves during the weekdays were 55.1%, 43.0% and 1.9% for M-, N- and E-types, respectively. Overall, bedtime, sleep onset time, wake-up time and get-up time during the weekdays were 21:04, 21:26, 6:55 and 6:59, respectively. Nocturnal sleep period, time in bed (TIB) and 24 h TIB (TIB and nap) during the weekdays were 9.49, 9.93 and 10.55 h, respectively. Sleep–wake timings were significantly and linearly delayed from M-, N-, to E-types ( p < 0.001). The weekday 24 h TIB (10.47–10.66 h) and weekend nocturnal sleep period (9.58–9.76 h) did not differ significantly among chronotypes. For E-types, socially advanced weekdays rising times (approximately 1 h) caused nocturnal sleep deficit (0.57 h). Children's socially scheduled times (e.g. start and finish times, mealtimes and daytime nap) and their parents' diurnal preferences had significant adjusted odds ratios among E-types, while the significant unadjusted odds ratios for morning sunlight and multimedia exposure disappeared. These results suggest the importance of chronobiologically planned sleep discipline at home as well as assessment of socially scheduled times in children.